Molecular docking of eleven snake venom peptides targeting human immunodeficiency virus capsid glycoprotein as inhibitors - Mousa O. Germoush; Maged Fouda; Mohammad J. S. Mantargi; Moustafa Sarhan; Barakat M. Alrashdi; Diaa Massoud; Sarah Alzwain; Nehmat Ghaboura; Ahmed E. Altyar; Mohamed M. Abdel-Daim (Open Veterinary Journal)
Background: Snake venoms are mainly composed of a mixture of proteins and peptides with antiviral activity against several viruses including HIV. Therefore, snake venoms represent promising source for new antiviral drugs.